Tourist satisfaction and loyalty in the hotel business: An application to the island of São Miguel, Azores - Maria da Graça Batista; João Pedro Couto; Diana Botelho; Cláudia Faias (Tourism & Management Studies)
This paper analyses the influence of service quality on customer satisfaction and loyalty. Questionnaires were used to retrieve data were used to construct a model of structural equations to test the perception of quality, satisfaction and subsequent loyalty of tourists. The results suggest that the main influential variables of satisfaction were the quality of service offered and how management dealt with complaints. The factors that contributed most to tourist loyalty were affective commitment, satisfaction, price, complaint management and the image of the hotel itself. The findings highlight factors that can be used as indicators of how managers can generate added value for their customers.